How many larvae and nymphs of Amblyomma spp. ticks (Ixodida: Ixodidae) are needed to detect the presence of Rickettsia (Rickettsiales: Rickettsiaceae)? - Barrantes, Gilbert (2019)
Tick-borne rickettsiosis is becoming a common emergent disease in many tropical countries, and the rapid detection of this disease could reduce the impact on wild life and public health. Pools of larvae and nymphs, and individual adult ticks are used for detection of Rickettsia species (Rickettsiaceae), but the number of larvae and nymphs in the pools likely affect the probability of detection of Rickettsia spp. We tested whether the number of larvae or nymphs of Amblyomma (Ixodidae) included in the pools affected the probability of detection. The number of larvae in each pool did not affect the probability of detecting Rickettsia spp., but the probability of detection increased rapidly with the number of nymphs. In this study, 20 nymphs are enough to approach a probability of 1 of detecting Rickettsia